2022
DOI: 10.1088/1742-6596/2408/1/012018
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic field in electric and hybrid cars

Abstract: In recent years rapid development of electromobility has been observed and hybrid and electric cars are becoming more and more popular. Their attractiveness is influenced by the reduction of exhaust gas emissions thanks to the use of electric drives. However, the use of this type of drive also raises some concerns, because people using this type of transport are in close proximity to the vehicle's electrical installation, which generates an electromagnetic field. High current values, up to several hundred ampe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…These measurements were used to calculate the induced electric fields of adult and infant passengers. Sztafrowski and Winiarz [18] studied the distribution of magnetic flux density in different seating positions of electric and hybrid electric vehicles under different operating conditions. Bae and Park [19] studied the electromagnetic environment generated by the wired charging systems of electric vehicles with different charging speeds and showed that the magnetic flux density generated by standard chargers was higher than that of fast chargers.…”
Section: Introductionmentioning
confidence: 99%
“…These measurements were used to calculate the induced electric fields of adult and infant passengers. Sztafrowski and Winiarz [18] studied the distribution of magnetic flux density in different seating positions of electric and hybrid electric vehicles under different operating conditions. Bae and Park [19] studied the electromagnetic environment generated by the wired charging systems of electric vehicles with different charging speeds and showed that the magnetic flux density generated by standard chargers was higher than that of fast chargers.…”
Section: Introductionmentioning
confidence: 99%